Radošās darbības veicināšana izšūšanas apguvē mājturībā un tehnoloģijās sākumskolā - Statņuka, Irina (Latvijas Universitāte, 2013)
Diplomdarba tēma „ Radošās darbības veicināšana izšūšanas apguvē mājturībā un tehnoloģijās sākumskolā.” Autores diplomdarba pētījuma mērķis, izpētīt radošās darbības veicināšanas iespējas izšūšanas apguvē mājturībā un tehnoloģijās sākumskolā. Diplomdarba teorētiskajā daļā apskatīti radošās darbības skaidrojumi pedagogu un psihologu teorētiskajās atziņās. Analizēti radošuma attīstības sekmēšanas pedagoģiski psiholoģiskie nosacījumi pētāmās problēmas aspektā. Praktiskajā daļā izveidots tematiskais plāns 4.klasei izšūšanā mājturībā un tehnoloģijās, veikta tā aprobācija un analizēti rezultāti. Atslēgvārdi:, radošās personības būtība, radošās darbības veicināšana, izšūšana, mājturība un tehnoloģijas.

The topic of the diploma paper is „Promoting the creative activity in the acquisition of embroidery in lessons of housekeeping and technologies in elementary school”. The aim of the diploma paper is to study the possibilities of promoting the creative activity in the acquisition of embroidery in lessons of housekeeping and technologies in elementary school. In the theoretical part of the diploma paper the descriptions of the creative activity in the theoretical conclusions of teachers and psychologists. The pedagogically psychological conditions of promoting the development of creativity have been analyzed in the aspect of the problem to be studied. In the practical part of the work a themed embroidery lesson plan was made for the 4th form students in housekeeping and technologies, the approbation was carried out and the results were analyzed. Key words: the essence of the creative personality, the promotion of the creative activity, embroidery, housekeeping and technologies.
Promoting the creative activity in the acquisition of embroidery in lessons of housekeeping and technologies in elementary school
Keywords: Pedagoģija